PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON EXAMPLES UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 011 SIDOREJO KECAMATAN SIMPANG KANAN - Santoso, Budi; Kurniaman, Otang; Daud, Damanhuri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The problem in this research is still lower social studies, social studies learning more centered on the teacher, exercises are given more routine and in the process of student learning more passive. It was seen from the percentage of test scores of students who reach KKM in class IV SDN 011 Sidorejo Simpang Kanan districts is 41.67% of the 12 students with an average value was 63.33. The school is defined KKM 65. From these problems need to be carried out action research with cooperative learning model examples of non examples